AN OBSERVATIONAL STUDY ON EMPIRICAL THERAPY IN ICU PATIENTS WITH SEPSIS IN A TERTIARY CARE HOSPITAL - SHABARAYA, A. R.; SUNKADAKATTE, MINCHU ARUNKUMAR; FERNANDES, JESSICA MARYIOLA; ADIYODI, CHANDANNA K.; N. P., MUHAMMED SHAMIL; TANTRY, SUDHAMSHU K. (International Journal of Current Pharmaceutical Research, 2026)
Objective: Sepsis is a life-threatening organ dysfunction caused by dysregulated host response to an infection. This study investigated antibiotic prescribing patterns, antimicrobial resistance, and their impact on prognosis and quality of life in critically ill patients with sepsis. Methods: A prospective observational study was conducted at Srinivas Institute of Medical Science and Research Centre. For over six months, 174 ICU patients diagnosed with sepsis were assessed. Patient demographics, infection source, Sequential Organ Failure Assessment (SOFA) scores, antibiotic regimens, and clinical outcomes were collected. Results: The study population was predominantly male (69.54%) with a mean age of 54 y. Piperacillin/Tazobactam (46.55%) and Meropenem (36.78%), both classified as WHO Watch antibiotics of AWaRe Classifications, were the most commonly prescribed antibiotics. This suggests a potential deviation from WHO guidelines and raises concerns about antibiotic resistance. Pseudomonas (15%) was the leading pathogen, exhibiting high resistance levels. While SOFA scores did not significantly differ between survivors and non-survivors, they correlated with length of stay, indicating disease severity. The SF-20 questionnaire revealed poor health perception and reduced social functioning across all age groups in surviving patients, impacting quality of life. Conclusion: This study highlights a trend of over-prescription of broad-spectrum antibiotics, potentially deviating from WHO recommendations. The dominance of highly resistant g-negative bacteria underscores the need for targeted antibiotic selection based on local resistance patterns. SOFA scores reflected disease severity but did not predict mortality. The study emphasizes the lasting impact of sepsis on patients' physical, social, and mental well-being, suggesting the importance of comprehensive post-discharge rehabilitation programs.